Giant panda BAC library construction and assembly of a 650-kb contig spanning major histocompatibility complex class II region - Zeng, Chang-Jun (BioMed Central, 2007)
BACKGROUND: Giant panda is rare and endangered species endemic to China. The low rates of reproductive success and infectious disease resistance have severely hampered the development of captive and wild populations of the giant panda. The major histocompatibility complex (MHC) plays important roles in immune response and reproductive system such as mate choice and mother-fetus bio-compatibility. It is thus essential to understand genetic details of the giant panda MHC. Construction of a bacterial artificial chromosome (BAC) library will provide a new tool for panda genome physical mapping and thus facilitate understanding of panda MHC genes. RESULTS: A giant panda BAC library consisting of 205,800 clones has been constructed. The average insert size was calculated to be 97 kb based on the examination of 174 randomly selected clones, indicating that the giant panda library contained 6.8-fold genome equivalents. Screening of the library with 16 giant panda PCR primer pairs revealed 6.4 positive clones per locus, in good agreement with an expected 6.8-fold genomic coverage of the library. Based on this BAC library, we constructed a contig map of the giant panda MHC class II region from BTNL2 to DAXX spanning about 650 kb by a three-step method: (1) PCR-based screening of the BAC library with primers from homologous MHC class II gene loci, end sequences and BAC clone shotgun sequences, (2) DNA sequencing validation of positive clones, and (3) restriction digest fingerprinting verification of inter-clone overlapping. CONCLUSION: The identifications of genes and genomic regions of interest are greatly favored by the availability of this giant panda BAC library. The giant panda BAC library thus provides a useful platform for physical mapping, genome sequencing or complex analysis of targeted genomic regions. The 650 kb sequence-ready BAC contig map of the giant panda MHC class II region from BTNL2 to DAXX, verified by the three-step method, offers a powerful tool for further studies on the giant panda MHC class II genes.